The Contemporary Muslim between The Middle Ages and Modernity - Azad Raouf Qazaz (IAIN SYEKH NUR JATI, 2024)
This article delves into a crucial aspect of Islamic thought—the dynamic interplay between text and reality, with a particular focus on the Quranic text. It explores the implicit or explicit adherence to the idea that the fixed text, especially the Quran, holds supremacy over the ever-changing reality. The intricate relationship between text and reality has far-reaching implications for intellectual, scientific, and societal transformations throughout the history of human knowledge. This work aims to spotlight significant shifts and pivotal moments in human thought, driven by fundamental changes in how the relationship between text and reality is perceived. It argues that the accumulation of ideas from human experiences unlocks doors to unexplored realms that were previously overlooked. Here,